Culturally sensitive adaptation of the concept of relational communication therapy as a support to language development: An exploratory study in collaboration with a Tanzanian orphanage - Ulrike Schütte (South African Journal of Communication Disorders, 2016)
Background: Orphans and other vulnerable children (OVC) who grow up in institutional care often show communication and language problems. The caregivers lack training, and there are few language didactics programmes aimed at supporting communication and language development in OVC in institutional care in Tanzania.